Effect of training load on simulated team sport match performance - Slattery, K. M.; Wallace, L. K.; Bentley, D. J.; Coutts, A. J. (Applied Physiology, Nutrition, and Metabolism, 2012)
This study examined the effect of training load on running performance and plasma markers of anaerobic metabolism, muscle damage, and inflammation during a simulated team sport match performance. Seven team sport athletes (maximal oxygen uptake, 47.6 ± 4.2 mL/kg·min) completed a 60-min simulated team sport match before and after either 4 days of HIGH or LOW training loads. Venous blood samples were taken pre-match, immediately post-match, and 2 h post-match for interlukin-6, monocyte chemoattractant protein-1 (MCP-1), creatine kinase (CK), lactate dehydrogenase, C-reactive protein, xanthine oxidase (XO), and hypoxanthine. Following HIGH training load, sprint velocity decreased (p < 0.001) and total distance covered was reduced (HIGH 5495 ± 670 m, LOW 5608 ± 674 m, p = 0.02) was observed during the simulated match protocol compared with the LOW match simulation. Decreased performance capacity was accompanied by a significant increase in serum CK concentration (HIGH 290 ± 62 U/L, LOW 199 ± 33 U/L, p = 0.005). The HIGH training also resulted in a decreased post-match hypoxanthine and MCP-1 and an increase in XO concentration 2 h post-match. Four days of increased training load reduced running performance during the match simulation and altered the metabolic and inflammatory response to high-intensity intermittent exercise.